2013
DOI: 10.1159/000342637
|View full text |Cite
|
Sign up to set email alerts
|

Gum Chewing: Another Simple Potential Method for More Rapid Improvement of Postoperative Gastrointestinal Function

Abstract: Background: Sham feeding has been reported to enhance bowel motility. Here, to promote gastrointestinal function after postoperative ileus, the effect of gum chewing (GC) was evaluated. Methods: Literature search including PubMed, Embase, Science Citation Index, SpringerLink, and secondary sources. Fixed-effect and random-effects models were used to measure the pooled estimates. The test of heterogeneity was performed with the Q statistic. Stratified and sensitivity analyses were performed to explore heterogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 67 publications
2
16
0
1
Order By: Relevance
“…Furthermore, complication rates between these two types of surgeries differ significantly. Results from this trial provide similar results to other RCTs 2 4. However, this RCT included chewing gum before surgery, albeit only for 3 h. Investigating the duration of effect and possible dose–response for the anti-inflammatory effect of chewing gum is an intriguing avenue for further investigation.…”
Section: Commentarysupporting
confidence: 66%
“…Furthermore, complication rates between these two types of surgeries differ significantly. Results from this trial provide similar results to other RCTs 2 4. However, this RCT included chewing gum before surgery, albeit only for 3 h. Investigating the duration of effect and possible dose–response for the anti-inflammatory effect of chewing gum is an intriguing avenue for further investigation.…”
Section: Commentarysupporting
confidence: 66%
“…Gum chewing, as a proxy of sham feeding, is a very simple way used to accelerate gut motility M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT recovery after surgical operation. Several trials have indicated its effectiveness in reducing the duration of postoperative ileus and hospital stay (2,3). Gastroenterologists have also investigated its effect on capsule endoscopy, and it is reported that chewing-gum can significantly decrease gastric transit time and small bowel transit time during capsule endoscopy, and it may improve the chance of capsule reaching the caecum without affecting image quality (4).…”
Section: Introductionmentioning
confidence: 99%
“…In order to determine the effect and safety of CG in patients undergoing colorectal surgery, 11 meta-analyses [818] have been published previously. The characteristics and outcomes of these all meta-analyses have been summarized in Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…Previous systematic reviews [818] have been performed to address this issue, and shown that CG may be a safe and inexpensive approach to enhance return of intestinal function following colorectal resection and shorten the LOS. However, little attention had been paid on several important outcomes including time to first bowel sounds, time to first feeding, mortality, economic effect and quality of life (QoL) in these incomplete analyses [818].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation